In-Situ Deaeration towards Performance Stability of Capacitive Deionization Cells. (10th April 2018) - Caudill, Landon; Omosebi, A.; Gao, X.; Landon, James; Liu, K.
Abstract : The effects of system pressure on the performance stability of flow-through capacitive deionization (CDI) cells was investigated. Initial data showed that the highly porous carbon electrodes possessed air/oxygen in the micropores, and the increased system pressure boosts the gases solubility in saline solution and carries them out of the cell in the effluent. Upon applying a potential difference to the electrodes, capacitive-based ion adsorption occurs in competition with faradaic reactions that consume oxygen. Through the addition of backpressure, the rate of degradation decreases, allowing the cell to maintain its salt adsorption capacity (SAC) longer. The removal of oxygen from the pore space of the electrodes makes it no longer immediately accessible to faradaic reactions, thus hindering the rate of reactions and giving the competing ion adsorption an advantage that is progressively seen throughout the life of the cell.